Registering Ternate City People’s Traditional Knowledge as Property Rights - Ibrahim, Mardia; Yunus, Yahya; Budiono, Arief (Universitas Semarang, 2024)
Traditional knowledge is a subset of intellectual activity that stems from a country's collective ideas, opinions, or discoveries. This research aims to analyze: (1) The municipal government provides legal protection for intellectual property rights in traditional knowledge to increase the welfare of Ternate City inhabitants and (2) the potential for registering intellectual property rights related to traditional knowledge from 2019 to 2023 in Ternate City. The legislation method and the case approach were used in this empirical study. The most feasible way for the Indonesian government to protect traditional knowledge now is to strengthen the database on traditional knowledge. Special regulations are urgently needed that regulate the implementation of licensing procedures for users of Traditional Knowledge. The urgency of this research because It was found that from 2019 to 2023 in Ternate City, no traditional knowledge database yet existed. On this basis, there needs to be tactical steps from the Ternate City Regional Government in encouraging city branding about the utilization of traditional knowledge. The novelty of this research because Ternate has an abundant amount of traditional knowledge from its hundreds of ethnic groups that need to be legally protected but nearly zero traditional knowledge is processed with property rights. This paper is urgent and it contributes to science as it provides knowledge on how to legally protect this valuable knowledge.